Acquired inducible antimicrobial resistance in Gram-positive bacteria. (August 2012) - Chancey, Scott T; Zähner, Dorothea; Stephens, David S
A major contributor to the emergence of antibiotic resistance in Gram-positive bacterial pathogens is the expansion of acquired, inducible genetic elements. Although acquired, inducible antibiotic resistance is not new, the interest in its molecular basis has been accelerated by the widening distribution and often 'silent' spread of the elements responsible, the diagnostic challenges of such resistance and the mounting limitations of available agents to treat Gram-positive infections. Acquired, inducible antibiotic resistance elements belong to the accessory genome of a species and are horizontally acquired by transformation/recombination or through the transfer of mobile DNA elements. The two key, but mechanistically very different, induction mechanisms are: ribosome-sensed induction, characteristic of the macrolide–lincosamide–streptogramin B antibiotics and tetracycline resistance, leading to ribosomal modifications or efflux pump activation; and resistance by cell surface-associated sensing of β-lactams (e.g., oxacillin), glycopeptides (e.g., vancomycin) and the polypeptide bacitracin, leading to drug inactivation or resistance due to cell wall alterations.